THE EFFECTIVENESS OF "FLASH CARD" IN IMPROVING MOTHERS’ KNOWLEDGE ON PREGNANCY - Tatarini Ika Pipitcahyani; Citra Adityarini Safitri (Proceedings of the International Conference on Applied Science and Health, 2017)
Background: The government has been supporting expecting mothers by providing pregnancy education courses in order to improve the quality of mother and child health and to reduce maternal mortality rate (MMR) and infant mortality rate (IMR). However, the existing activities are felt to be ineffective to accelerate the decline of MMR and IMR, therefore the government is reorganising its program by emphasising in knowledge and changes in mother and family behaviour. With the increase of awareness and behavioural change, it is expected that the public are more alert of the importance of pregnancy health. Aims: To know the effectiveness of using flash cards as a method to educate the expecting mothers during pregnancy counselling class. Methods: The study used pre-experimental pre-test and post-test control group designed with the intervention using flash card. This study was conducted from January to September 2016 with a population of 40 pregnant women and sampling by means of accidental sampling with 10 respondent. The research was designed by using Quasi-Experiment Wilcoxon statistical techniques. Results: From Wilcoxon test, the results demonstrate a level of knowledge in the control group with a score of 0.59 sig (p>0.05). In the treatment group sig 0.05 (p>0.005) indicates a significant difference between the group using flip charts and the flash card group. From the Mann-Whitney test, the results yield sig 0.002 (p>0.005) which shows that flash card proved to increase the level of knowledge of pregnancy. Conclusion: Counselling using a flash card is an effective method to educate the expecting mothers to better understand the knowledge of pregnancy health.